2018
DOI: 10.1016/j.ultsonch.2017.08.023
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of dispersion behavior of agglomerated particles in liquid between ultrasonic irradiation and mechanical stirring

Abstract: The particle dispersion behavior was compared for ultrasonic irradiation and mechanical stirring. The experiment and calculation were carried out with polymethylmethacrylate (PMMA) particles. The dispersion rate of the agglomerated particles increased with the decreasing ultrasonic frequency and the increasing electric power, whereas it increased with the increasing rotation speed for the mechanical stirring. The temporal change in the particle dispersion proceeded stably after passage of a long time. The disp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(40 citation statements)
references
References 25 publications
0
39
0
1
Order By: Relevance
“…Ultrasonic wave specific function is to provide reaction energy to reduce reaction temperature and disperse particles [28] , [30] , [34] . Previous study have shown that the dispersion rate of the produced particles increased with the increasing electric power for the ultrasonic irradiation [42] . A.L.Nikolaev, et al [43] researched results shown high power ultrasound regime provide smaller nucleation sites and smaller resulting particles, compared to vortices and particles obtained without ultrasound.…”
Section: Resultsmentioning
confidence: 84%
“…Ultrasonic wave specific function is to provide reaction energy to reduce reaction temperature and disperse particles [28] , [30] , [34] . Previous study have shown that the dispersion rate of the produced particles increased with the increasing electric power for the ultrasonic irradiation [42] . A.L.Nikolaev, et al [43] researched results shown high power ultrasound regime provide smaller nucleation sites and smaller resulting particles, compared to vortices and particles obtained without ultrasound.…”
Section: Resultsmentioning
confidence: 84%
“…Conventional physical and mechanical dispersion methods, such as ball and jet milling, contaminate the dispersion because of a high milling speed and are ineffective in achieving complete dispersion of the nanoparticles [4,5]. As a result, contactless dispersion methods using ultrasonic dispersion equipment are frequently employed.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the understanding and application of particle dispersion methodologies is important. The conventional physical and mechanical dispersion methods such as ball milling and jet milling contaminate the dispersion of nanoparticles due to high milling speed and ineffectiveness [1,2]. Interest in fundamental and applied research on nanoparticle dispersion using ultrasonic waves has been increasing.…”
Section: Introductionmentioning
confidence: 99%